2019
DOI: 10.1021/acs.orglett.9b01866
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical, Manganese-Assisted Carbon–Carbon Bond Formation between β-Keto Esters and Silyl Enol Ethers

Abstract: The electrochemical carbon–carbon bond formation process between β-keto esters and silyl enol ethers was investigated utilizing manganese salts. The tricarbonyl compounds were generated in moderate to good yields under neutral conditions. Control experiments revealed that an electro-generated base at the cathode is important. Electroanalytical measurements with a Mn­(TPA) complex suggested that the oxidation of the silyl enol ether is the first step in the oxidation process initiated by a corresponding Mn­(IV)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…A couple of years ago we reported the cerium‐catalyzed oxidative coupling of β‐oxoesters 1 with olefins like styrene [7] or enol acetates 2 [8] furnishing products 3 with a 1,4‐diketone moiety (Scheme 1). An electrochemical version of this transformation with silyl enol ethers was also reported [9] . Recently, we have discovered the formation of δ‐lactones 4 with an 1,4‐dicarbonyl moiety in the side chain when acetophenone derived enol ethers like compound 2 a , were submitted to this aerobic coupling reaction with β‐oxoesters 1 [10] .…”
Section: Introductionmentioning
confidence: 79%
“…A couple of years ago we reported the cerium‐catalyzed oxidative coupling of β‐oxoesters 1 with olefins like styrene [7] or enol acetates 2 [8] furnishing products 3 with a 1,4‐diketone moiety (Scheme 1). An electrochemical version of this transformation with silyl enol ethers was also reported [9] . Recently, we have discovered the formation of δ‐lactones 4 with an 1,4‐dicarbonyl moiety in the side chain when acetophenone derived enol ethers like compound 2 a , were submitted to this aerobic coupling reaction with β‐oxoesters 1 [10] .…”
Section: Introductionmentioning
confidence: 79%
“…To commence our studies, 1-phenylcyclobutan-1-ol 1 was selected as the model substrate (Table ). After extensive optimization, it was found that an electrochemical system composed of MnCl 2 .4H 2 O (10 mol %) as catalyst, MgCl 2 (5 equiv) as chloride source, and LiClO 4 as supporting electrolyte in MeCN/AcOH (7:1, [ 1 ] = 0.05 M) using galvanostatic conditions ( i = 10 mA, j anode = 7.8 mA/cm 2 , Q = 3.73 F/mol) and graphite electrodes at 25 °C for 3 h under N 2 , enabled the deconstructive chlorination of 1 , giving γ-chlorinated ketone 2 in 82% NMR yield (entry 1). No conversion occurs in the absence of electricity or the manganese catalyst (entries 2 and 3).…”
mentioning
confidence: 99%
“…In collaboration with Prof. J. Christoffers (Oldenburg University) we investigated an electrochemical carbon-carbon bond formation assisted by manganese(III) acetate in acetonitrile (Scheme 17). [23] Scheme 14. Convergent paired electrolysis in a quasi-divided cell in a threecomponent reaction.…”
Section: Manganese-assisted Carbonà Carbon Bond Formationmentioning
confidence: 99%
“…In collaboration with Prof. J. Christoffers (Oldenburg University) we investigated an electrochemical carbon‐carbon bond formation assisted by manganese(III) acetate in acetonitrile (Scheme ) …”
Section: Lesson From the Refereesmentioning
confidence: 99%